2018
DOI: 10.3389/fpsyg.2018.00129
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Depression: Action Video Game Play May Reduce Rumination and Increase Subjective and Objective Cognition in Depressed Patients

Abstract: Cognitive deficits are common in depression and may persist following the resolution of affective symptoms. However, therapeutic strategies that successfully target cognitive impairments are lacking. Recent work has demonstrated that playing action video games leads to improvements in cognition, in particular executive function, in healthy individuals. We therefore set out to test whether playing video games can reduce symptoms associated with depression. We focussed on depressive symptoms and on rumination, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 52 publications
0
55
0
2
Order By: Relevance
“…On a cortical level, Benady-Chorney et al ( 2018 ) observed that habitual video game players (who played ≥ 6 h/week for a 6 month period) compared to non-habitual video game players (who played ≤ 6 h/week for a 6 month period) had greater cortical thickness in the dorsal anterior cingulate cortex, which is associated with enhanced learning and attentional control. The lack of a positive result in Kühn et al ( 2018 ) perhaps suggests the gameplay duration (6 weeks vs. 6 months in Benady-Chorney et al, 2018 ) may not have induced sufficient cortical activation for cognitive enhancements and subsequent reduction of rumination (and depressive symptoms).…”
Section: Impact Of Gameplay Durationmentioning
confidence: 96%
See 3 more Smart Citations
“…On a cortical level, Benady-Chorney et al ( 2018 ) observed that habitual video game players (who played ≥ 6 h/week for a 6 month period) compared to non-habitual video game players (who played ≤ 6 h/week for a 6 month period) had greater cortical thickness in the dorsal anterior cingulate cortex, which is associated with enhanced learning and attentional control. The lack of a positive result in Kühn et al ( 2018 ) perhaps suggests the gameplay duration (6 weeks vs. 6 months in Benady-Chorney et al, 2018 ) may not have induced sufficient cortical activation for cognitive enhancements and subsequent reduction of rumination (and depressive symptoms).…”
Section: Impact Of Gameplay Durationmentioning
confidence: 96%
“…Indeed, a meta-analysis by Powers et al ( 2013 ) on the effects of video game play on information processing highlighted how the genre of the video game can influence how effective the video game is at enhancing aspects of cognitive functioning (e.g., auditory and visual processing, executive functions, and spatial imagery). Kühn et al ( 2018 ) used an action video game, a genre that Powers et al ( 2013 ) reported had a moderate effect size (Cohen's d = 0.22–0.62) with respect to cognitive functioning. Research has shown that general cognitive activation and executive functioning are more linked to games that involved learning patterns and logical puzzles, components not found in Boson X, than those that are classified as action video games (Mondéjar et al, 2016 ).…”
Section: Impact Of Genrementioning
confidence: 99%
See 2 more Smart Citations
“…Videogames are considered the most popular pastime activity of the last two decades (Granic, Lobel, & Engels, 2014), with an emerging trend to their exploitation for neurorehabilitation purposes, both in cognitive and sensorimotor domains (Horne-Moyer, Moyer, Messer, & Messer, 2014), as well as for neuropsychiatric disorders (Kühn, Berna, Lüdtke, Gallinat, & Moritz, 2018). According to cross-sectional evidence in healthy individuals, videogaming induces several cognitive-behavioral effects, enhancing skills such as selective attention (Green & Bavelier, 2003), short-term memory (Boot, Kramer, Simons, Fabiani, & Gratton, 2008), spatial cognition (Greenfield, 2009), multitasking (Green & Bavelier, 2006a), task-switching (Green & Bavelier, 2012), decision-making (Green, Pouget, & Bavelier, 2010), and cognitive control (Anguera et al, 2013).…”
Section: Introductionmentioning
confidence: 99%